Efektivitas penggunaan beberapa mikroba terhadap pertumbuhan dan analisis pertumbuhan tanaman ubi jalar (Ipomoea batatas L.) var. cilembu - Retno Tri Purnamasari; Dewi Asmarani; Sri Hariningsih Pratiwi (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2025)
This study aims to determine the optimal dosage of several effective microbes in increasing the growth and growth analysis of sweet potato (Ipomoea batatas L.) Cilembu variety. The study was conducted on Jl. Raya Bromo, Pasrepan 1 Hamlet, Pasrepan District, Pasuruan Regency, at an altitude of about 600-800 meters above sea level with an average temperature of 22°C to 32°C. This study took place from October 2024 to April 2025. The method used in this study was a Randomized Block Design (RAK) with one factor consisting of four treatments and six replications. The treatments given included; P0: control (without microbial administration), P1: administration of microbes at a dose of 3 g l-1, P2: administration of microbes at a dose of 5 g l-1, and P3: administration of microbes at a dose of 7 g l-1. The data obtained were analyzed using analysis of variance (F test) at the 5% level. If a significant effect is found, the Least Significant Difference (LSD) test is performed at a 5% level. The results showed that the use of several microbes at a dose of 5 g l-1was the most effective dose in increasing the growth of Cilembu sweet potato plants. The 5 g l-1 dose produced the highest results in various growth parameters, including vine length, leaf number, leaf area, dry weight of the upper and lower parts of the plant, and leaf area index. Furthermore, this treatment also resulted in a higher plant growth rate compared to other treatments. The use of higher doses did not always result in significant increases, so the 5 g l-1 dose can be recommended as the best treatment to support optimal sweet potato growth.